Debating on Transport Corridors of Azerbaijan in the Context of Globalization - Rahil Dadaşlı; Orkhan Valiyev (Universal Journal of History and Culture)
This paper investigates the impact of globalization on transportation corridors in Azerbaijan, which are strategically located to serve as hubs for crossroads between north-south and east-west trade. The main hypothesis is that globalization has had a significant impact on transportation corridors in Azerbaijan, resulting in greater connectivity and trade flows within the region. The recent triumph over Armenia has resulted in significant changes in the region, enhancing Azerbaijan's reputation. Alongside the ongoing conflict in Ukraine and the imposition of sanctions on Russia and Iran, Azerbaijan has emerged as a secure passage between these influential powers. Furthermore, the rising demands for major international trade routes have created a pressing need for Azerbaijan to enhance its capabilities to effectively meet these growing requirements. According to the World Systems Theory, semi-periphery countries play the role of bridges between core and periphery states. Globalization has led to Azerbaijan's integration into the global economic system as a semi-peripheral country. This has resulted in increased trade and investment, which in turn has led to the development of transportation infrastructure and the expansion of transportation networks.